2005
DOI: 10.1146/annurev.publhealth.26.021304.144357
|View full text |Cite
|
Sign up to set email alerts
|

ADOLESCENT RESILIENCE: A Framework for Understanding Healthy Development in the Face of Risk

Abstract: Key Words positive development, protective factors, alcohol, tobacco, illegal drugs, sexual behavior, violent behavior ■ Abstract Adolescent resilience research differs from risk research by focusing on the assets and resources that enable some adolescents to overcome the negative effects of risk exposure. We discuss three models of resilience-the compensatory, protective, and challenge models-and describe how resilience differs from related concepts. We describe issues and limitations related to resilience an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

115
1,771
2
152

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 2,101 publications
(2,118 citation statements)
references
References 118 publications
115
1,771
2
152
Order By: Relevance
“…Our data corroborate this view; 53% reported zero or only one psychosocial health problem. A recent review of adolescent resilience research found virtually no studies of gay, lesbian, bisexual, or transgender youth, leaving a significant void in the literature (40). It is critical that future research identifies the internal and external strengths that lead to such resilience in the face of documented stressors and societal stigma.…”
Section: Discussionmentioning
confidence: 99%
“…Our data corroborate this view; 53% reported zero or only one psychosocial health problem. A recent review of adolescent resilience research found virtually no studies of gay, lesbian, bisexual, or transgender youth, leaving a significant void in the literature (40). It is critical that future research identifies the internal and external strengths that lead to such resilience in the face of documented stressors and societal stigma.…”
Section: Discussionmentioning
confidence: 99%
“…Our focus on protective resilience limited analysis to those young men who did not experience, at the time of data collection, psychosocial health outcomes associated with heightened HIV risk. Future research might consider looking at compensatory resilience (Fergus and Zimmerman, 2005), or those resources and assets that may counteract syndemic exposure. Research along these lines would examine how GBM with multiple syndemic conditions navigate to more supportive environments and remain sexually safe.…”
Section: Limitationsmentioning
confidence: 99%
“…Models of resilience (i.e., Fergus & Zimmerman, 2005;Howard, Budge, & McKay, 2010) highlight the importance of identifying factors that buffer or reduce the effects of risk factors on children. This study supports the role of the mother-child relationship as a protective factor that may reduce aggressive beliefs, which mediate the link between exposure to violence and aggressive behavior.…”
Section: Discussionmentioning
confidence: 99%
“…The goal of the present study was to examine whether secure mother-child attachment predicts less accepting attitudes about aggression in the context of children's experiences with aggression in the home and in the community. We examined whether secure attachment uniquely predicted children's beliefs after accounting for their exposure to aggression, which Fergus and Zimmerman (2005) labeled a "compensatory effect" or moderated the association between exposure to aggression and their attitudes about the justifiability of aggressive behavior (a "protective effect"; Fergus & Zimmerman, 2005). In addition, we tested a full moderatedmediation model to determine if secure attachment buffered the effects of violence on attitudes and if aggressive attitudes mediated the relationship between exposure to violence and aggressive behaviors.…”
mentioning
confidence: 99%